Enhancing the Implementation of the Mapping, Outreach, Advocacy, and Registration (PESIAR) Program through a Lean Six Sigma Approach : A Qualitative Study - Maihendra; Arsaythamby Veloo; Mohamad Fazali bin Ghazali (CV. Get Press Indonesia, 2026)
Universal Health Coverage (UHC) remains a major global health policy objective, yet many countries still encounter implementation challenges that hinder equitable service coverage and financial protection at the local level (World Health Organization & World Bank, 2025). In Indonesia, the national health insurance program managed by BPJS Kesehatan has achieved significant expansion; however, disparities across regions and gaps in enrollment and active participation persist within the decentralized governance system (Agustina et al., 2019). To address these challenges, BPJS Kesehatan introduced the PESIAR program (Mapping–Outreach/Sweep–Advocacy–Registration), an outreach-based enrollment strategy emphasizing cross-sector collaboration and operational effectiveness (BPJS Kesehatan, 2023). This qualitative case study examines how Lean Six Sigma (LSS) supports the strengthening of PESIAR implementation at the Bukittinggi Branch, West Sumatra. Data were collected through semi-structured interviews, field observations, and document analysis, and were thematically analyzed using a DMAIC framework (Define–Measure–Analyze–Improve–Control) (Antony et al., 2019). Findings show that LSS enhances program implementation by improving governance processes, clarifying stakeholder responsibilities, and strengthening performance measurement systems. Expanding JKN membership is therefore influenced not only by outreach intensity but also by structured, data-driven management approaches. Continuous improvement emerges as a key requirement for managing complex, multi-stakeholder health programs aimed at achieving UHC. Lean Six Sigma further contributes by fostering an organizational culture that continuously identifies and addresses operational challenges, supporting sustainable health system governance (Purdue University, 2024).